The Effect of Tax Audit, Tax Amnesty, and Tax Sanctions on Taxpayer Compliance at Pratama Bima Tax Services Office - Khas Sukma Mulya; Muhammad Rizkan; Fitriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aims to analyze the effect of tax audits, tax amnesty, and tax sanctions on taxpayer compliance at the Bima Pratama Tax Service Office. This study uses primary data and secondary data. Preliminary data were obtained through each respondent's answers, and secondary data was obtained from KPP Pratama Bima related to the number of individual registered taxpayers, taxpayers subject to SPT, and taxpayers reporting SPT. The samples in this study were 92 individual taxpayers registered at KPP Pratama Bima. Data were analyzed using the SPSS statistical program. These results indicate that simultaneously and partially, the tax audit, tax amnesty, and tax sanctions variables positively and significantly affect individual taxpayer compliance.